Effect of eculizumab treatment in patients with paroxysmal nocturnal hemoglobinuria with or without high disease activity: Real‐world findings from the International Paroxysmal Nocturnal Hemoglobinuria Registry. (21st June 2022) - Höchsmann, Britta; de Fontbrune, Flore Sicre; Lee, Jong Wook; Kulagin, Alexander D.; Hillmen, Peter; Wilson, Amanda; Marantz, Jing L.; Schrezenmeier, Hubert
Abstract: Background: The effects of eculizumab treatment in paroxysmal nocturnal hemoglobinuria (PNH) patients with or without high‐disease activity (HDA), defined by LDH ≥ 1.5 × ULN and history of major adverse vascular events (MAVEs; including thrombotic events [TEs]); anemia; and/or physician‐reported abdominal pain, dyspnea, dysphagia, erectile dysfunction, fatigue, and/or hemoglobinuria, in the International PNH Registry were evaluated. Methods: Registry patients were stratified by baseline HDA and eculizumab‐treatment status. Longitudinal changes in laboratory and clinical PNH‐related endpoints were evaluated using linear mixed models (continuous variables) or Poisson regression (incidence rates). Results: As of May 1, 2017, 3009 patients (HDA/eculizumab‐treated, n  = 913; HDA/never‐treated, n  = 651; no‐HDA/eculizumab‐treated, n  = 173; no‐HDA/never‐treated, n  = 1272) were analyzed. Higher proportions of eculizumab‐treated patients had HDA and history of MAVEs. In patients with and without HDA, respectively, eculizumab treatment resulted in reductions from baseline for (1) LDH ratio (mean [SD]: −5.3 [4.0] and −2.3 [3.8]); (2) incidence rate ratio (IRR) for MAVEs (−80% and −70%); (3) IRR for TEs (−80% for both); and (4) units of red blood cell transfusions per year (from 6.8 to 2.8 and 3.6 to 2.5 units). Conclusions: Eculizumab treatment in a real‐world setting improved outcomes, including substantial decreases in hemolysis, MAVE rates, TEs, and transfusions in PNH patients regardless of HDA.